2019
DOI: 10.1007/s10714-019-2510-9
|View full text |Cite
|
Sign up to set email alerts
|

Stellar tidal disruption events in general relativity

Abstract: A tidal disruption event (TDE) ensues when a star passes too close to the supermassive black hole (SMBH) in a galactic center and is ripped apart by the tidal field of the SMBH. The gaseous debris produced in a TDE can power a bright electromagnetic flare as it is accreted by the SMBH; so far, several dozen TDE candidates have been observed. For SMBHs with masses above ∼ 10 7 M , the tidal disruption of solar-type stars occurs within ten gravitational radii of the SMBH, implying that general relativity (GR) is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 237 publications
(331 reference statements)
2
83
0
Order By: Relevance
“…The most relativistic encounter shown in this work is a β = 3 disruption of a ZAMS Sun; here r p 14GM BH /c 2 . In this regime, relativistic effects on the rate of return of the fallback material are minor (Tejeda et al 2017;Stone et al 2019). Note also that in our simulations the tidal radius is 100R , meaning that the BH enters the computational domain as it moves through pericenter.…”
Section: Methodsmentioning
confidence: 99%
“…The most relativistic encounter shown in this work is a β = 3 disruption of a ZAMS Sun; here r p 14GM BH /c 2 . In this regime, relativistic effects on the rate of return of the fallback material are minor (Tejeda et al 2017;Stone et al 2019). Note also that in our simulations the tidal radius is 100R , meaning that the BH enters the computational domain as it moves through pericenter.…”
Section: Methodsmentioning
confidence: 99%
“…The x = ±1, a = 1 polynomial was previously given in factorized form in Eq. (24). The roots are all real, and they are (ordered by value)…”
Section: Number Of Real Equatorial Roots and Bracketsmentioning
confidence: 99%
“…Parabolic encounters are astrophysically interesting for modeling tidal disruptions of ordinary stars around supermassive black holes [23][24][25]. They are also interesting as potential sources of gravitational wave bursts [26,27].…”
Section: E Parabolic Trajectoriesmentioning
confidence: 99%
“…The fits are given in terms of functions of the penetration factor β (the first four being analogous to the A 5/3 , B 5/3 , C 5/3 and D 5/3 given by GRR13), and follow the scaling with the BH size M, the stellar mass m and radius r , the radiative efficiency and the canonical energy spread ∆E ref (Eq. 1 with k E = 1 and n = 0) given by GRR13 and Stone et al (2019):…”
Section: Appendix A: Fitting Parametersmentioning
confidence: 99%
“…The importance of general relativistic effects has recently been reviewed by Stone et al (2019), whereas results from simulations are summarized by Lodato et al (2015) and recent observational advances on TDEs can be found in Komossa (2015). 2,3,4,5,6,7,8,9,10, 11} BH spin a {−0.99, −0.5, 0, 0.5, 0.99} SPH particles N part 200 642 2 METHOD…”
Section: Introductionmentioning
confidence: 99%